A STUDY ON STUDENTS’ PREFERENCE OF ENGLISH LECTURERS’ LANGUAGE USED IN ENGLISH CLASSROOMS - Sonia Lisia; Jismulatif Jismulatif; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research investigates the use of L1 in English Study Program, University of Riau. This study aims to know students’ preference, the frequency used and students’ reasons for the use of L1 in English classrooms. This study applied survey designed. The population of this research was the second-fourth-sixth-semester students of the English study program of Teachers’ Training and Education Faculty of Universitas Riau with a total number of population is 344 students. The number of the sample in this research was 120 students. Data was collected by using an online questionnaire and interviews. Data was analyzed by using Microsoft Excel. The results showed that the majority of students suggested English must be used and a small percentage of students suggested using L1 to make them easier to understand the materials taught by lecturers.Key Words: English, English classrooms, L1, Students’ Preference, Students’ Reason